2018
DOI: 10.1007/s00270-018-1890-7
|View full text |Cite
|
Sign up to set email alerts
|

Volume Reduction in Enlarged Kidneys in Autosomal Dominant Polycystic Kidney Disease (ADPKD) Prior to Renal Transplant with Transcatheter Arterial Embolization (TAE): A Systematic Review and Meta-Analysis

Abstract: Current studies conclude that TAE is an effective and minimally invasive option for reduction in renal volume in order to optimize patient outcome for renal transplantation and for relief of compression symptoms. Further prospective studies involving increased sample size and multiple centers should be pursued to establish evidence-based guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Ye at al. (13) described in a systematic review and meta-analysis of the literature on TAE for ADPKD that all studies demonstrated similar success rates in renal volume reduction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ye at al. (13) described in a systematic review and meta-analysis of the literature on TAE for ADPKD that all studies demonstrated similar success rates in renal volume reduction.…”
Section: Discussionmentioning
confidence: 98%
“…As to the embolic agents used in TAE for ADPKD, various agents have been employed in previous studies (3,7,(11)(12)(13). These included coils (3,10), absolute ethanol (7,11), and polyvinyl alcohol particles (12).…”
Section: Discussionmentioning
confidence: 99%
“…Other indications for kidney embolization in pediatric nephrology are arterial aneurysms and arteriovenous malformations, functional exclusion and polycystic kidney disease before transplantation, angiomyolipoma (mainly in the context of tuberous sclerosis), and autosomal dominant polycystic kidney disease (ADPKD) before kidney transplantation [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all individuals are candidates for this procedure. Transcatheter arterial embolization (TAE) of the renal arteries may provide a noninvasive method of reducing renal volume in ADPKD [ 119 ].…”
Section: Interventionmentioning
confidence: 99%